(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Cryptography and data security have been used to make data more secure for many years, military communications are having a major impact on growing cryptography field. Although the internet have been invited in the ends 1960’s, but it is not appear to public until invent the World Wide Web (www) in 1989. The World Wide Web allows people to e-mail each other and transfer data. This appeared as one reason in growing use of computer. In addition needs to make e-commerce more secure. Cryptography understanding helps to find better ways or protocols to make transfer data faster and more efficient. This paper starts with a brief background about security and cryptography. It provides central concepts of cryptography. Also provides an account of substitution techniques algorithms and their implementation. The implementation will be as an application in c# language that reads a text, encodes it by a specified algorithm and decodes the encrypted text. In addition explaining the mathematical functions used in the algorithms